GUN1 Controls Accumulation of the Plastid Ribosomal Protein S1 at the Protein Level and Interacts with Proteins Involved in Plastid Protein Homeostasis. Issue 3 (28th January 2016) - Tadini, Luca; Pesaresi, Paolo; Kleine, Tatjana; Rossi, Fabio; Guljamow, Arthur; Sommer, Frederik; Mühlhaus, Timo; Schroda, Michael; Masiero, Simona; Pribil, Mathias; Rothbart, Maxi; Hedtke, Boris; et al.
Abstract : The gene product associated with a so-called Genomes UNcoupled (gun) mutant interacts with proteins involved in plastid protein homeostasis. Abstract: Developmental or metabolic changes in chloroplasts can have profound effects on the rest of the plant cell. Such intracellular responses are associated with signals that originate in chloroplasts and convey information on their physiological status to the nucleus, which leads to large-scale changes in gene expression (retrograde signaling). A screen designed to identify components of retrograde signaling resulted in the discovery of the so-called genomes uncoupled ( gun ) mutants. Genetic evidence suggests that the chloroplast protein GUN1 integrates signals derived from perturbations in plastid redox state, plastid gene expression, and tetrapyrrole biosynthesis (TPB ) in Arabidopsis ( Arabidopsis thaliana ) seedlings, exerting biogenic control of chloroplast functions. However, the molecular mechanism by which GUN1 integrates retrograde signaling in the chloroplast is unclear. Here we show that GUN1 also operates in adult plants, contributing to operational control of chloroplasts. The gun1 mutation genetically interacts with mutations of genes for the chloroplast ribosomal proteins S1 (PRPS1) and L11. Analysis of gun1 prps1 lines indicates that GUN1 controls PRPS1 accumulation at the protein level. The GUN1 protein physically interacts with proteins involved in chloroplast protein homeostasis based on coimmunoprecipitation experiments. Furthermore, yeast two-hybrid and bimolecular fluorescence complementation experiments suggest that GUN1 might transiently interact with several TPB enzymes, including Mg-chelatase subunit D (CHLD) and two other TPB enzymes known to activate retrograde signaling. Moreover, the association of PRPS1 and CHLD with protein complexes is modulated by GUN1. These findings allow us to speculate that retrograde signaling might involve GUN1-dependent formation of protein complexes.